The effect of gas hydrates self-preservation in the process of their industrial development - Zezekalo, Ivan; Kobolev, Volodymyr; Lukin, Oleksandr; Vynnykov, Yuriy; Safronov, Anatoly (Academic journal Industrial Machine Building Civil Engineering, 2022)
The negative influence of the gas hydrates (GH) self-preservation effect  on the course of the technological process of their industrial development by the depressurization method is considered. The main parameters of the self-preservation  manifestation: the porosity of the hydrate and its morphological characteristics are justified. An important practical conclusion was made that solving the problems of gas hydrates self-preservation  should be facilitated by the selection of the optimal operation mode for the production well, which would harmonize the hydrate porosity  and its morphological characteristics, and at the same time ensure the maximum possible production and control over the processes of gas hydrates dissociation.
Keywords: gas hydrates; development of gas hydrate; deposits; self-preservation; ice crust; parameters of self-preservation manifestation during mining